ChemInform Abstract: Iridium(III)‐Catalyzed C—H Amidation of Arylphosphoryls Leading to a P‐Stereogenic Center. Issue 13 (March 2015) - Gwon, Donghyeon; Lee, Donggun; Kim, Jiyu; Park, Sehoon; Chang, Sukbok
Abstract An iridium(III)‐catalyst system allows the direct amidation of arylphosphoryls with various sulfonyl azides under mild conditions and for the first time in an asymmetric manner.